A novel quantitative real-time PCR method for identification and quantification of mammalian and poultry species in foods. (June 2017) - Ren, Yifei; Li, Xiang; Liu, Yueming; Yang, Litao; Cai, Yicun; Quan, Sheng; Pan, Liangwen; Chen, Shunsheng
Abstract: Meat adulteration has posed considerable risks to public health. In this study, we developed a novel real-time quantitative PCR method for the detection of some mammalian and poultry species that are used as meat products or meat adulterants. The method was based on the detection of the single-copy nuclear gene myostatin . The specificity, heterogeneity, and copy number of myostatin were evaluated. Additionally, we determined the sensitivity and precision of the method. The results revealed that myostatin had high specificity and low heterogeneity among different mammalian and poultry species. The limit of detection was 5 pg of animal genomic DNA or 0.001% meat ingredient, and the limit of quantification was 10 pg of animal genomic DNA or 0.01% meat ingredient. The quantification results of 12 blind samples showed that the biases between the measured and true values were <25%. Therefore, the developed quantitative real-time PCR method for mammalian and poultry species is suitable for identification and quantification of different meat ingredients as a reference gene. Highlights: A real-time PCR method for mammalian and poultry species detection was developed. It was suitable for total mammalian and poultry ingredients quantification in foods. It was based on the detection of the single-copy nuclear gene myostatin. It could be used in identification and quantification of meat adulteration.